Political economy of infrastructure investment allocation: evidence from a panel of large German cities - Achim Kemmerling; Andreas Stephan (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
This paper proposes a simultaneous-equation approach to the estimation of the contribution of infrastructure accumulation to private production. A political-economy model for the allocation of public infrastructure investment grants is formulated. Our empirical findings, using a panel of large German cities for the years 1980, 1986, and 1988, suggest that cities ruled by a council sharing the State (.Bundesland.) government's current political affiliation were particularly successful in attracting infrastructure investment grants. With regard to the contribution of infrastructure accumulation to growth, we find that public capital is a significant factor for private production. Moreover, at least for the sample studied, we find that simultaneity between output and public capital is weak; thus, feedback effects from output to infrastructure are negligible. – – Dieses Papier verwendet ein simultanes Gleichungssystem zur Schätzung des Beitrags von Infrastrukturinvestitionen zu regionalem Wachstum. Ein polit-ökonomisches Modell der Allokation von Finanzzuweisungen für öffentliche Investitionen in Infrastruktur wird formuliert. Unsere empirischen Ergebnisse basierend auf einem Paneldatensatz für große deutsche Städte in den Jahren 1980, 1986 und 1988 deuten darauf hin, dass Städte, deren Mehrheit im Stadtrat die selbe politische .Couleur. wie die Landesregierung hatte, erfolgreicher bei der Zuteilung von Finanzzuweisungen waren. Im Hinblick auf den Beitrag der Infrastrukturakkumulation auf das Wachstum finden wir, dass öffentliches Kapital ein wichtiger Faktor für die private Produktion ist. Weiterhin, zumindest für den untersuchten Zeitraum, finden wir, dass die Simultanität zwischen Output und öffentlichem Kapital gering ist; daher sind Feedback-Effekte von Output zur Infrastruktur vernachlässigbar.
Keywords: 330